ECONOMIC GROWTH AND PROSPERITY: ARABIC AND ISLAMIC STUDIES PERSPECTIVE - Busari, Kehinde Kamorudeen (UIN Walisongo Semarang, 2024)
The Islamic world has a rich history of economic thought that has evolved over centuries, and the unique perspective of Arabic and Islamic studies provides valuable insights into contemporary economic challenges. Islamic economics, rooted in the teachings of the Qur'an and Hadith, emphasizes ethical and moral principles in economic activities. Central to this perspective is the concept of